Pengaruh model pembelajaran think talk write (ttw) dan motivasi belajar terhadap keterampilan menulis pantun pada kelas IV SD - Nurul Asmahul Sholihah; St Y Slamet; Lies Lestari (Didaktika Dwija Indria, 2022)
The purpose of this research is to finds out the effect of Think Talk Write (TTW) model and learning motivation on pantun writing skills. This form of research is a quasi-experimental. The population in this research is the fourth grades students of Public Elementary School in Laweyan district. Sampling techniques is using cluster random sampling. Data collection techniques are using tests and questionnaire. Data analysis technique is using two ways anova. The results revealed that the Think Talk Write (TTW) model give a positive effect on pantun writing skills (FA = 6,55 > Ftabel = 4,09), the learning motivation give a positive effect on pantun writing skills (FB = 45,74 > Ftabel = 4,09), and there is interaction between model of learning and learning motivation on pantun writing skills (FAB = 4,17 > Ftabel = 4,09). Based on the result of the research, it can be concluded that the Think Talk Write (TTW) model and learning motivation give a positive effect on pantun writing skills. The implication of this research is that the Think Talk Write model can be an alternative in learning to write, because it is proven to have a good influence on pantun writing skills.Keyword : Think Talk Write (TTW), learning motivation, pantun writing skills, elementary school